Pós-graduação no Brasil e a formação acadêmica: percepções de egressos de um mestrado profissional - Souza, Quezia Alves de (2024)
The process of evaluating postgraduate programs, carried out by the Coordination for the Improvement of Higher Education Personnel (CAPES), requires information from program graduates. As part of the evaluation, CAPES takes into account the situation of the graduates, i.e. the destination, performance and evaluation of the graduates of the program in relation to the training received. In this sense, this study aims to analyze the perceptions of the graduates of the Graduate Program in Public Policy, Management and Evaluation of Higher Education (PPGAES) on aspects related to the training they received in the program. To this end, the methodology for conducting the study is based on a qualitative approach, based on bibliographical and documentary research. The study was conducted with PPGAES graduates and used a questionnaire as a data collection instrument. The study population included graduates of the program between 2015 and 2021. Closed-ended questions were analyzed by tabulating the frequency of responses, and open-ended questions were subjected to Bardin's (2011) content analysis according to the theme of the question. The study showed that the contributions and skills developed during their training were: "knowledge acquisition", "salary increase", "professional performance", "functional advancement", "participation in events and publication of articles", "enhancement of teaching and academic career", "reading and writing skills", "research skills", and "development of critical sense". The graduates perceived a significant improvement in personal aspects and, consequently, in professional and academic aspects. The majority of graduates rated the quality of the PPGAES as "excellent" and "good," indicating a positive evaluation of the dimensions analyzed. The most highly rated dimensions were "secretarial service", "relationship with advisor" and "teacher attendance". The items with the lowest percentages were "library", "equipment", and "infrastructure". The qualification of the teaching staff and the practical application of the professional master's research were the strengths most often mentioned by the graduates, while the workload of the courses and the lack of encouragement to publish were considered the weakest aspects of the program. Thus, we can conclude that the PPGAES was positively evaluated and considered of great importance for the personal, professional and academic development of the graduates. With regard to the identification of weaknesses, these can be used as a source of knowledge to promote continuous improvement of the program.